2016
DOI: 10.1002/ajoc.201500438
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Oxazolidine Derivatives by [3+2]‐Annulation Reactions of 1‐Tosyl‐2‐phenyl/alkylaziridines with Aryl Epoxides

Abstract: An efficient methodf or the synthesis of oxazolidine derivatives from aziridines and in situ generateda ldehydes from Meinwald rearrangements of the epoxides has been developed. This methodg ives easy access to function-alized oxazolidines,w hich are constitutional moieties present in severaln atural products and biologically active molecules. The scope of the title transformation has also been elaborated with av ariety of substrates.Scheme1.Synthetic approaches to oxazolidine derivatives.N BS = N-bromosuccini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The isomerization into the corresponding carbonyl analogs is usually referred to as the Meinwald rearrangement . Due to its excellent efficiency and atom economy, this reaction has gained relevance for the synthesis of carbonyl compounds, ring expansion reactions, and tandem processes . The Lewis acid‐promoted Meinwald rearrangement has found application in fine chemistry and industrial processes .…”
Section: Figurementioning
confidence: 99%
“…The isomerization into the corresponding carbonyl analogs is usually referred to as the Meinwald rearrangement . Due to its excellent efficiency and atom economy, this reaction has gained relevance for the synthesis of carbonyl compounds, ring expansion reactions, and tandem processes . The Lewis acid‐promoted Meinwald rearrangement has found application in fine chemistry and industrial processes .…”
Section: Figurementioning
confidence: 99%
“…[22] However, these compounds are also widely used in organic synthesis as a chiral ligand in some catalyzed reactions such as aza-Michael reaction, [23] oxidation reactions, [24] Friedel-Crafts reaction, [25] allylation [26] and Diels-Alder reaction. [27] Some procedures for the synthesis of the oxazolidines are Lewis acid catalyzed [3 + 2] annulation of ketones with aziridines, [28,29] and geminal difunctionalization of vinyl arenes. [30] Thus, due to the impor-tance of the oxazolidine derivatives in organic synthesis and medicinal chemistry, many researchers have focused their attention to the synthesis, isolation and application of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, they are also broadly exploited as chiral auxiliaries, ligands and organocatalysts in asymmetric synthesis and catalysis. 5–8 Several strategies have been reported to assemble these heterocyclic motifs which include: [3 + 2]-annulation reactions, 9,10 1,3-dipolar cycloaddition, 11,12 the condensation reaction of 1,2-amino alcohol/diamine derivatives with carbonyl compounds, 5,13,14 the aza -Wacker reaction, 15 etc. In 2011, Xiao et al reported sp 3 C–H bond functionalisation of the N -CH 2 Ph (benzylic) group and subsequent intramolecular cyclisation of 1-2-diamines using a Ru-based photocatalyst in the presence of a strong base (Fig.…”
Section: Introductionmentioning
confidence: 99%